TechnoSecurity's Guide to E-Discovery and Digital Forensics : a Comprehensive Handbook. - Wiles, Jack (Elsevier, 2007)
Complete coverage of e-discovery, a growth market, from the people that run the TechnoForensics annual tradeshow.